2003
DOI: 10.1080/15401420390844500
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Very Low Doses of Cisplatin on Tumor Cell ProliferationIn Vitroand on Some Hematological and Enzymatic Parameters of Healthy Rats

Abstract: Healthy rats had been treated for 2 or 6 weeks with 1.0 mL of and 10-l6 mg/ mL of cisplatin. After 2 weeks of treatment, a significant increase in leukocyte and erythrocyte count and also in hematocrit was observed. Among leukocytes the number of neutrophils and eosinophils significantly increased. Biochemical analyses indicated a decrease in the glycogen content in the liver and kidneys after 2 weeks of treatment with low doses of cisplatin but at the end of the experiment (8th week of experiment) the stores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The main molecular mechanism of cisplatin is myelotoxicity is due to its ability to bind with cellular DNA and render the cell incapable of replication [20]. Beside this, another mechanism of cisplatin is its ability to induce oxidative stress [21]. Reactive oxygen species are toxic to bone marrow cells and probably can trigger apoptosis and affect cell cycle, causing anemia and a decrease in leukocyte count [22].…”
Section: Discussionmentioning
confidence: 99%
“…The main molecular mechanism of cisplatin is myelotoxicity is due to its ability to bind with cellular DNA and render the cell incapable of replication [20]. Beside this, another mechanism of cisplatin is its ability to induce oxidative stress [21]. Reactive oxygen species are toxic to bone marrow cells and probably can trigger apoptosis and affect cell cycle, causing anemia and a decrease in leukocyte count [22].…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin alone treatment caused significant reduction in RBC counts with subsequent decline in Hb concentration and PCV which is a known side-effects induced by cisplatin in the hosts [47]. Therapeutic doses of cisplatin are evidently toxic to bone marrow cells and probably can trigger apoptosis and affect cell cycle causing an anemia and a decrease in WBC count [48]. In present study, treatment with the combination of rutin and cisplatin showed significant improvement in all the hematological values indicating its potential to reduce cisplatin-induced hematotoxicities (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Antitumor drugs are known to suppress hematopoiesis. Cis-Pt caused hematotoxicity at both low (10 -8 -10 -12 g/ml per rat) [36] and high (4-16 mg/kg) concentrations [34,[37][38][39], with the development of anemic conditions both in intact and tumorbearing animals. In our study, Cis-Pt in a total dose of 3.75 mg/kg aggravated anemia in LLC-bearing mice as evidenced by the reduction of hemoglobin and erythrocyte levels by 21% and 20%, respectively, and lymphocytopenia (Table 2).…”
Section: The Survival Of Llc-bearing Mice Treated With Cis-pt and C 6...mentioning
confidence: 99%